Characteristics of Humbert, the Hero of Vladimir Nabokov's Lolita Novel (Vladimir Nabokov'un Lolita romanının kahramanı Humbert'in özellikleri) - Basira AZIZALIYEVA (Altralang Journal, 2020)
ABSTRACT: “Lolita” written by Vladimir Nabokov has been considered as an important occasion in the history of world literature for its theme and concept of its characters. The novel written in an original way with distinctive creativity has been subject to debates and various evaluations. Humbert is one of the main characters in the novel “Lolita” with literary mission, serving to demonstrate several psychological, moral and physiological problems, reflecting reasons and effects of various problems that were actual for the society during that time. Since “Lolita” was written during the period when postmodernism influence was observed in the works of Nabokov, it is very noticeable to find postmodern tendencies in the writer’s style and in his main character. Freud’s psychoanalytic theory and its interpretation have played a crucial role in revealing Humbert’s specificity. While assesing Humbert in this context, author’s original approach becomes apparent due to some occasions which are caused by psychological and physiological problems. For this purpose, research on interpretation of Humbert’s stance showed that Humbert’s attitude towards Lolita and his controversial traits are presented in comparison with Freud psychoanalytic theory. Comparative analysis has showed that Humbert is a character who directly affects interpretation of characters and evaluation of events.  So, it involves tendencies of that time and takes upon a mission to analyze existing wishes of human that can’t be openly expressed and to reveal threats that are triggered by those traits.